Attribution Patterns in Women With and Without Orgasmic Difficulties. Issue 6 (24th July 2018) - Rowland, David L.; Medina, Mia C.; Dabbs, Christopher R.
Abstract : People with sexual problems are more likely to attribute negative sexual experiences to themselves, in contrast with sexually functional individuals who attribute negative sexual experiences to external factors such as the circumstance or situation. We investigated attribution patterns in women reporting difficult or absent orgasm—a group only minimally investigated in this regard—to determine whether they differed from women without orgasmic problems. Using an internet-based approach, we compared attribution responses of 376 women with orgasmic difficulty with 367 women without orgasmic difficulty to five sexual scenarios, two presenting positive sexual experiences and three presenting negative sexual experiences. Women with orgasmic difficulty were more likely to take blame for any negative sexual experience, including ones not related to orgasmic difficulty. They were also more likely to attribute responsibility to their partner's lack of skill, whereas orgasmic women attributed negative outcomes more to circumstance. Women with orgasmic difficulty were also less likely to assume credit or responsibility for positive sexual experiences. Differences between orgasmic and non-orgasmic groups persisted or were augmented when age and arousal difficulty were controlled. These results emphasize the stark contrast in the way women with and without orgasmic problems approach sexual situations and suggest several therapeutic strategies.